2015
DOI: 10.1007/s10071-015-0894-9
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory discrimination and generalization of ammonium nitrate and structurally related odorants in Labrador retrievers

Abstract: A critical aspect of canine explosive detection involves the animal's ability respond to novel, untrained odors based on prior experience with training odors. In the current study, adult Labrador retrievers (N = 15) were initially trained to discriminate between a rewarded odor (vanillin) and an unrewarded odor (ethanol) by manipulating scented objects with their nose in order to receive a food reward using a canine-adapted discrimination training apparatus. All dogs successfully learned this olfactory discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…In addition, the dogs' 579 perception of the mixture stimulus in our study suggest that dogs perceive the mixture as a new 580 odor rather than as its individual elements. Consistent with previous behavioral studies, this 581 may explain why dogs trained on individual target odors have difficulty generalizing to mixtures 582(Lazarowski & Dorman, 2014;Lazarowski et al, 2015). Further, dogs' brain activations showed 583 more similarity between the mixture of odors and a no reward odor, suggesting either a584 learned association or a neural bias toward the no reward (distractor) odor.…”
supporting
confidence: 73%
“…In addition, the dogs' 579 perception of the mixture stimulus in our study suggest that dogs perceive the mixture as a new 580 odor rather than as its individual elements. Consistent with previous behavioral studies, this 581 may explain why dogs trained on individual target odors have difficulty generalizing to mixtures 582(Lazarowski & Dorman, 2014;Lazarowski et al, 2015). Further, dogs' brain activations showed 583 more similarity between the mixture of odors and a no reward odor, suggesting either a584 learned association or a neural bias toward the no reward (distractor) odor.…”
supporting
confidence: 73%
“…The dogs initially took part in an olfaction study. Details of that study, including housing and husbandry, have already been published . The median weight of the cohort was 26.2 kg (range: 24.2–28 kg).…”
Section: Methodsmentioning
confidence: 99%
“…Within breed variation is commonly highlighted in the literature (Björnerfeldt et al 2008;Barnard et al 2017), including within breed variation for odour discrimination ability (Lazarowski et al 2015). Our results also demonstrated that individual variation was prominent in all breeds.…”
Section: Discussionsupporting
confidence: 77%
“…The large degree of individual variation within breeds, both during training and accuracy testing, was not anticipated. Previous studies have highlighted the degree of individual variation within breeds (Björnerfeldt et al 2008;Barnard et al 2017), including their odour discrimination ability (Lazarowski et al 2015). Due to this study's small sample size, however, broad conclusions cannot yet be drawn on specific dog breed's trainability or working suitability.…”
Section: Aim 3 -Breed Comparisonmentioning
confidence: 99%